2013
DOI: 10.1108/er-12-2012-0095
|View full text |Cite
|
Sign up to set email alerts
|

Can public relations improve the workplace? Measuring the impact of stewardship on the employer-employee relationship

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…Prior literature demonstrated that low LMXSC can physiologically damaging for the focal employee resulting in low commitment and low satisfaction (Eisenberger, Stinglhamber, Vandenberghe, Sucharski, and Rhoades, 2002;Rousseau, 1989), more critical behavior (Waters, Bortree, & Tindall, 2013), greater separation from the leader, low positive effects, reduced performance and commitment, reduced trust towards the supervisor and the organization (Rowold & Rohmann, 2009), and ultimately looks for solutions outside the organization. Similarly, individuals with low LMXSC develop low trust of the organization and become apprehensive that the leaders may underestimate their valuable suggestions (Detert & Burris, 2007), as such, they may resort to silent behavior in the organization due to apprehension.…”
Section: The Mediating Role Of the Employee-organization Relationshipmentioning
confidence: 99%
“…Prior literature demonstrated that low LMXSC can physiologically damaging for the focal employee resulting in low commitment and low satisfaction (Eisenberger, Stinglhamber, Vandenberghe, Sucharski, and Rhoades, 2002;Rousseau, 1989), more critical behavior (Waters, Bortree, & Tindall, 2013), greater separation from the leader, low positive effects, reduced performance and commitment, reduced trust towards the supervisor and the organization (Rowold & Rohmann, 2009), and ultimately looks for solutions outside the organization. Similarly, individuals with low LMXSC develop low trust of the organization and become apprehensive that the leaders may underestimate their valuable suggestions (Detert & Burris, 2007), as such, they may resort to silent behavior in the organization due to apprehension.…”
Section: The Mediating Role Of the Employee-organization Relationshipmentioning
confidence: 99%
“…An EOR is, "…a connection or association between an organisation and individual employees that necessitates repeated communication" (Rhee, 2007, p. 11). Waters, Bortree & Tindall (2013) assessed the impact of stewardship on EORs and observed that greater involvement from employees and stewardship from employers had a positive impact on EOR assessment.…”
Section: Literaturementioning
confidence: 99%
“…In addition to the meaningful exchange of business and process tasks, communication processes also contain another interpersonal side, and successful communication has to achieve yet another goal, which is to develop mutual trust among the participants in the communication process, increase the degree of acceptance and friendship (Waters et al, 2013).…”
Section: Introductionmentioning
confidence: 99%